The Relationship between Psychological Resilience, Psychological Adaptation and Purpose in Life among University Students in the Preparatory Year - Alsadi, Rihab Aref; Drabie, Ahmad Ismail (American Journal of Education and Learning, 2020)
The study aimed to show the correlational relationship between psychological resilience and both of psychological adaptation and purpose in life among university students in the preparatory year, and to make sure of the relative contribution of psychological resilience in predicting psychological adaptation and purpose in life. The sample of the study consisted of(304) university students in the preparatory year from both sexes. They were chosen by the random cluster sample method, and their ages ranged between(18-19) years. The study concluded that there is a strong and positive relationship between psychological resilience and psychological adaptation for preparatory year students, where the level of significance (0.000) and correlation coefficient (0.491), and there is a strong and positive relationship between psychological resilience and purpose in life for preparatory year students, where the level of significance (0.000) and correlation coefficient (0.549). The results of the study also showed that psychological resilience interprets a percentage of(24%) of psychological adaptation. Also interprets psychological resilience interprets a percentage of (30%) of purpose in life.